Studi transposisi didaktik terhadap mahasiswa calon guru matematika: Tinjauan pada konteks knowledge to be taught dalam konsep turunan - Prihandhika, Aditya; Fatimah, Ade Evi; Sujata, Tatang (Mahesa Research Center, 2023)
The concept of derivatives is an important concept in the field of Calculus to be studied and taught at school and university levels. However, understanding derived concepts that do not fully involve the meaning of various representations has the potential to trigger a combination of concept descriptions with formal concept definitions as well as learning challenges or learning obstacles in epistemological, ontogenic and also didactic aspects. Therefore, the research carried out aims to observe the context of the knowledge that will be taught as one of a series of didactic transposition processes in order to obtain transpositional knowledge that is relevant to be taught. The research method used is qualitative research with a hermeneutic phenomenological approach. The participants involved in the research were 38 students who were prospective mathematics teachers from one of the universities in West Java. The research results show that there are inaccuracies in the presentation of ideas and concepts related to the knowledge to be taught, especially in the definition of derivative concepts. The mismatch between formal concept definitions and participant concept descriptions in learning by referring to mathematics textbooks which are used as the main reference results in learning obstacles for the subjects so that there is a need for repersonalization and recontextualization as an effort to produce more meaningful knowledge.